EXPLAINING THE ROLE OF SERVICE QUALITY AND CUSTOMER VALUE ON CUSTOMER SATISFACTION - Cahyono, Tri; Herdinata, Christian; Harianto, Eric; Olasode, Tikristini (Jurnal Aplikasi Manajemen, 2023)
The interest of this study is how to maintain service quality to achieve customer satisfaction. This study is expected to provide an understanding of the effect of service quality and customer value on customer satisfaction and its indicators. This study analyzes the factors influencing customer satisfaction in the aviation training and education industry. The studies were on service quality, customer value, and customer satisfaction. This research is descriptive and quantitative and focuses on analyzing factors that influence customer satisfaction with a survey method approach using a questionnaire. The population in this study were alumni of Merpati Training Centre students who had completed the initial FOO and Engineering education held by Merpati Training Centre. The study was conducted on 86 respondents with a non-random sampling technique using purposive sampling. The results of the study showed that the service quality has a significant effect on customer value, the service quality has a significant effect on customer satisfaction, the customer value has a significant effect on customer satisfaction, and the service quality has a significant effect on customer satisfaction through the intervening customer value. It showed that maintaining good relationships with customers, in this case, students, and improving the service quality provided will impact the customer value obtained by students. Ultimately the expected customer satisfaction is achieved in the aviation training and education industry. If the service quality, customer value, and customer satisfaction are met as expected, it will impact increasing the number of customers and growing in the future.